Pelanggan TV Berbayar di Indonesia: Tantangan Hambatan Berpindah dalam Mempertahankan Loyalitas - Wahyuddin, Nisaa Nursyabanniyah; Hurriyati, Ratih; Lisnawati, Lisnawati (Journal of Business Management Education (JBME), 2019)
This present study aims to describe switching barrier and customer loyalty of Pay TV in Indonesia. This study uses a descriptive approach with the explanatory survey method. The unit of analysis for Paid TV’s Customer is 108 respondents. Data collection using a questionnaire. The data analysis technique is using a simple linear regression with SPSS 24.0 for Windows program tools. Based on the results of the study, it can be known that the switching barrier has a partial effect on the customer loyalty with a high influence category. The difference in this study lies in the object of research, research time, measuring instruments, literature used, theory used and research results.Keywords: Customer Loyalty; Pay TV; Switching Barrier